2014
DOI: 10.1080/07399332.2014.959168
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Increasing Cervical Cancer Screening Amongst First Nations Communities in Northwest Ontario, Canada

Abstract: The high burden of cervical cancer in Indigenous populations worldwide is due to underscreening and inadequate follow-up. Using qualitative, participatory action research, we interviewed health care staff to identify ways to increase screening recruitment in First Nations communities in Northwest Ontario, Canada. Our findings suggest the value of a multilevel social-ecological model to promote behavioral changes at the community, health care service and stakeholder, and decision-maker level. Participants empha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 37 publications
1
23
0
5
Order By: Relevance
“…We reasoned that empowering women to take their own samples may help overcome some of the structural and cultural barriers First Nations women face when attending cervical screening 13 —a re-affirmed notion and deemed to be culturally appropriate by our community informants during the qualitative phase of the ACCSS. 17 18 DNA integrity from self-samples was excellent—an important factor to emphasise when promoting this screening method as some women reported being anxious that they were not taking their self-sample correctly. Greater than 95% of the samples could be HPV-tested and typed, confirming our earlier pilot data.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that empowering women to take their own samples may help overcome some of the structural and cultural barriers First Nations women face when attending cervical screening 13 —a re-affirmed notion and deemed to be culturally appropriate by our community informants during the qualitative phase of the ACCSS. 17 18 DNA integrity from self-samples was excellent—an important factor to emphasise when promoting this screening method as some women reported being anxious that they were not taking their self-sample correctly. Greater than 95% of the samples could be HPV-tested and typed, confirming our earlier pilot data.…”
Section: Discussionmentioning
confidence: 99%
“…It is also highly accepted by women because it is more discrete and less invasive than physician-obtained samples [45]. Furthermore, self-sampling "has the potential to further empower women to collect their own samples in privacy giving them control over how and when they participate in screening" [46]. HPV test results obtained in self-sampled material are highly concordant with those obtained by physicians [47][48][49][50][51].…”
Section: Modern Screening Methods To Overcome Disparitiesmentioning
confidence: 99%
“…We conducted interviews (lasting from 40 to 90 minutes) with 18 experienced, younger (under 40 years of age) and middle-aged (above 40 years of age) HCPs from August 2011 to February 2012 (Maar et al, 2013;Maar et al, 2014). We conducted nine focus groups (lasting from 80 to 120 minutes and including between 3 to 11 women at each community site) from May to July 2012 and then two additional ones in April and May 2014 to reach saturation with the focus group data.…”
Section: Participantsmentioning
confidence: 99%
“…We hypothesize that increased, regular screening attendance and follow-up of abnormal screening results would reduce the higher cervical cancer burden in this population. We have previously reported screening recruitment strategies with First Nations women and, based on interviews with health care professionals (HCPs), we have reported that education is one of the key factors for increasing their cervical screening attendance (Maar et al, 2013;Maar et al, 2014). To obtain a more representative and comprehensive understanding of the views held by members of our partner communities, we extended our study to include community members without formal health education to ensure that their voices would be heard in the research.…”
Section: Introductionmentioning
confidence: 99%